Food and Agriculture in Ethiopia : Progress and Policy Challenges - Rashid, Shahidur; Dorosh, Paul (Book collections on Project MUSE., 2013)
In this volume, policy experts provide empirical evidence to shed light on the complexities of agricultural and food policy in today's Ethiopia, highlight major policies and interventions of the past decade, and provide insights into building resilience to natural disasters and food crises.